The inclusion of water with the injected aerosol reduces the simulated effectiveness of marine cloud brightening. (17th May 2013) - Jenkins, A. K. L.; Forster, P. M.
Abstract: Sea‐salt aerosols proposed for injection in marine cloud brightening geoengineering would likely result from evaporation of sea‐water droplets. Previous simulations have omitted this mechanism. Using the WRF/Chem model (Weather Research and Forecasting model coupled with Chemistry) in large‐eddy simulation mode, we find that droplet evaporation creates cold pools, suppressing initial aerosol plume heights by up to 30% (40 m). This lessens cloud albedo increases from 94.1 to 88.5% in our weakly‐precipitating case and from 4.3 to 1.4% for daytime injection into our nonprecipitating case (cloud albedo differences of 0.012 and 0.009, respectively). Inclusion of this effect in future modelling would allow increasingly realistic effectiveness estimates.